2001
DOI: 10.1021/jo015543l
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Synthesis of a Methylene-Bridged Neu5Ac-α-(2,3)-Gal C-Disaccharide

Abstract: A general strategy toward the synthesis of C-ketosides of N-acetylneuraminic acid (Neu5Ac) has been developed and successfully applied to the synthesis of methylene-bridged Neu5Ac-alpha-(2,3)-Gal C-disaccharide 2. The key strategic element of this novel approach is a stereoselective, 6-exo-trig selective, electrophilic cyclization of the appropriate open chain precursor 4 by means of phenylselenyl triflate. The open chain precursor was formed by the addition of lithiated iodide 18 accessible from D-galactose t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 54 publications
0
27
0
Order By: Relevance
“…[9,[12][13][14][15] The processo fo btaining cyclic carbonates via the direct reaction between glycols and CO 2 is more sustainable and ecological than the reactionw ith epoxides or use of phosgene (COCl 2 ). [16][17][18] However,t his route has thermodynamic limitations and the yields are usually low if water suppressor agents are not used to shift equilibrium. [19] We have shown that NaY zeolite impregnated with Ag, Zn and Sn oxidesa re good catalysts for the direct carbonation of glycerolt og lycerol carbonate.…”
Section: Introductionmentioning
confidence: 99%
“…[9,[12][13][14][15] The processo fo btaining cyclic carbonates via the direct reaction between glycols and CO 2 is more sustainable and ecological than the reactionw ith epoxides or use of phosgene (COCl 2 ). [16][17][18] However,t his route has thermodynamic limitations and the yields are usually low if water suppressor agents are not used to shift equilibrium. [19] We have shown that NaY zeolite impregnated with Ag, Zn and Sn oxidesa re good catalysts for the direct carbonation of glycerolt og lycerol carbonate.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of synthetic chemists to construct desired glycoside bonds has progressed and has contributed to our understanding of the recognition mechanisms for receptor proteins and the development of enzyme inhibitors. [7][8][9][10] Sialylation is one of the most challenging reactions in carbohydrate chemistry and often proceeds with low yield and poor stereoselectivity. [11][12][13] In particular, the stereoselective synthesis of a-sialosides is complicated because sialic acid does not contain a neighboring C-3 functional group to direct the stereochemical outcome of the glycosylation.…”
Section: Introductionmentioning
confidence: 99%
“…Linhardt et al reported a convergent synthesis of CH(OH)-linked α(2,3)sialylgalactose 18 via SmI 2 -mediated coupling reaction [16] (Scheme 2). Schmidt et al reported a synthesis of CH 2 -linked α(2,3)sialylgalactose 19 via a linear synthetic sequence [17]. Since 18 was preparable very efficiently, we first planned to convert 18 into 21, and ketone 20 was prepared from alcohol 18 (Scheme 1).…”
Section: Novel Strategy For Constructing C-sialosidesmentioning
confidence: 99%